Assessing stakeholders’ needs for information from charity organisations / Saunah Zainon - Zainon, Saunah (Institute of Graduate Studies, UiTM, 2014)
Studies examining the extent of disclosure of NPOs remain sparse, yet it is essential to ensure accountability to stakeholders. This study was initiated to elicit stakeholders’ information needs from charity organisations. The research objectives include: to measure the extent of disclosure of information by charity organisation in Malaysia; to understand the motivating factors that drives the donors to donate; to determine reasons charity organisations disclose information about their organisation and to examine the organisational-specific attributes affecting the extent of information disclosed. A Charity Organisations Reporting Index (ChORI) instrument was developed to reliably measure the extent of information disclosure. Stakeholder theory and resource dependence theory were used in the development of the index. A complete set of ChORI items were compiled and used in a survey involving 117 institutional donors. The objective of the survey was to obtain the weight of importance of the items. The extent of disclosure was then measured by using both the unweighted and weighted index of the information items.